2017
DOI: 10.1074/jbc.c116.768549
|View full text |Cite|
|
Sign up to set email alerts
|

Functional specialization of two paralogous TAF12 variants by their selective association with SAGA and TFIID transcriptional regulatory complexes

Abstract: Edited by John M. Denu TATA box-binding protein (TBP)-associated factors (TAFs), evolutionarily conserved from yeast to humans, play a central role during transcription initiation. A subset of TAF proteins is shared in transcription factor II D (TFIID) and SAGA transcription regulatory complexes. Although higher eukaryotes contain multiple TAF variants that specify tissue-and developmental stage-specific organization of TFIID or SAGA complexes, in unicellular genomes, however, each TAF is encoded by a single g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In contrast, TAF9, TAF10 and TAF12 are shared between SAGA and TFIID in most species, although there are notable exceptions to this rule. A recent study has identified two paralogs of Taf12 in the human pathogenic yeast Candida albicans , each encoding a distinct protein, Taf12 and Taf12l, which specifically associates with TFIID or SAGA, respectively [28]. Furthermore, Schizosaccharomyces pombe (sp) has two paralogous Taf5 proteins, Taf5, which is found in both SAGA and TFIID, and Taf5l, which is only found in TFIID [29].…”
Section: Sharing the Core Structural Module Between Saga And Tfiidmentioning
confidence: 99%
“…In contrast, TAF9, TAF10 and TAF12 are shared between SAGA and TFIID in most species, although there are notable exceptions to this rule. A recent study has identified two paralogs of Taf12 in the human pathogenic yeast Candida albicans , each encoding a distinct protein, Taf12 and Taf12l, which specifically associates with TFIID or SAGA, respectively [28]. Furthermore, Schizosaccharomyces pombe (sp) has two paralogous Taf5 proteins, Taf5, which is found in both SAGA and TFIID, and Taf5l, which is only found in TFIID [29].…”
Section: Sharing the Core Structural Module Between Saga And Tfiidmentioning
confidence: 99%
“…The two Arabidopsis TAF12 proteins were recently shown to exhibit different affinities toward TFIID and SAGA components (42). The fungal pathogen Candida albicans also boasts two copies of TAF12 that participate in the growth of this unicellular organism nonredundantly, with each one showing selective interaction with the TFIID or SAGA complexes (43). Therefore, plants may also exploit multiple TAF12 isoforms for different purposes based on their interacting PIC subcomplexes, which may improve transcriptome plasticity and contribute to the strong environmental adaptability of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding construction of plasmids and C. albicans strains are available on request. Briefly, genes encoding the HAP complex subunits Hap2, Hap3, and Sef1 were genomically TAP-tagged in C. albicans strain SN152 using the plasmids Ip21 and Ip22 ( 25 ) as DNA templates and ONC645/646, ONC649/650, ONC637/638 respectively as primers and the tagging cassettes were amplified by PCR using Phusion HF DNA polymerase. Correct integration of the tagging cassettes in C. albicans strains KNC398, KNC410, and KNC379 was confirmed by PCR, and protein expression was confirmed by western blotting using rabbit polyclonal anti-TAP antibody (Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…This article contains supporting information ( 11 , 13 , 14 , 19 , 25 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ).…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation